The Prevalence of Myopia in Schoolchildren in Some Regions of Russia - O. P. Proskurina; E. Yu. Markova; V. V. Brzheskij; E. L. Efimova; M. N. Efimova; N. N. Chvatova; N. N. Slychalova; A. V. Egorova (Oftalʹmologiâ, 2018)
The frequency of myopia reached 26 % among of school graduates in 2000. In case of graduates from gymnasiums and lyceums — 50 %. The share of severe form of myopia 10–12 %. A pilot study was conducted. The prevalence of myopia was estimated in schoolchildren of 1, 5 and 11 classes in some Russian regions (Moscow, St. Petersburg, Igevsk, Ivanovo). Objectively cycloplegic refraction was studied in 3659 schoolchildren. During the entire period of being at school emmetropia was the most common type of refraction. In 5 and 11 classes myopia was more often refractive errors. The prevalence of myopia among 1th classes schoolchildren was 2.4 %, among 5th classes — 19.7 %, 11th classes — 38.6 %. In children studying in lyceums the prevalence of myopia was significantly higher (p < 0.01). Already in the 1 classes of gymnasiums and lyceums myopic children were 7.5 %, while in regular schools only 1.4 %. In 11 classes of lyceums the share of myopic children was 50.7%, in regular schools it was 30.9 %. This confirms the influence of education on the prevalence of myopia as an additive factor. The study of the myopia prevalence should be continued in different regions and municipalities to the subsequent development the rational programs for prevention of development and the progression of myopia in school.